Decision-making strategies for reperfusion therapies: navigating through stroke trials gaps - Pellegrino, Mateus Paquesse; Guerra, Felipe Borelli Del; Perissinotti, Iago Navas (Arquivos de Neuro-Psiquiatria, 2022)
Despite there being a robust amount of literature and numerous randomized clinical trials regarding acute ischemic stroke treatment, the trials have not included some frequent controversial situations for which decision-making strategies are an urgent and unmet need in clinical practice. This article tries to summarize the current evidence about some selected situations (mechanical thrombectomy in low ASPECTS, low NIHSS with proximal occlusion, acute basilar occlusion, distal and medium vessel occlusion, among others), make suggestions on how to approach them in clinical practice and show what to expect in acute stroke research in the near future.
Keywords: Stroke; Ischemic Stroke; Thrombectomy; Mechanical Thrombolysis; Thrombolytic Therapy